Implementation of the Concept of Balance at Kelenteng (Shrine) in Lasem - Subroto, T. Yoyok Wahyu (Department of Architecture and Planning, Faculty of Engineering, UGM, 2005)
This research aims to explore and to identify all about the Kelenteng (shrine)of Cu An Kiong, Poo An Bio and Gie Yong Bio in Lasem, Central Java. Based on empirical study, it is known that Taoism, Confusianism and Budhism cannot be apart from their culture and life where kelenteng becomes the place for conducting ritual activities. A fixed orientation of four cardinal directions such as east, west, south and north together with five basic elements of Taoism: water, fire, wood, metal and earth were harmonizing to set the building of kelenteng. It was becoming the basic cosmological concept consideration where the kelentengs have to be set.